The rise of political economy in the Scottish enlightenment - Sakamoto, Tatsuya, 1955-; Tanaka, Hideo, 1949- (London ; New York : Routledge, 2003)
This book seek to provides a comprehensive view of the rise and progress of political economy in eighteenth century Scotland with a special emphasis upon its internal connections with the Scotish enlightenment.
Andrew Fletcher's criticism of the commercial civilization and his plan for European federal union / Shigemi Muramatsu -- Policy debate on economic development in Scotland: the 1720's to the 1730's / Gentaro Seki -- Morality, polity and economy in Francis Hutcheson / Toshiaki Ogose -- Robert Wallace and the Irish and Scottish Enlightenment / Yoshio Nagai -- The ancient-modern controversy in the Scottish Enlightenment / Yasuo Amoh -- Hume's political economy as a system of manners / Tatsuya Sakamoto -- The 'Scottish Triangle' in the shaping of political economy: David Hume, Sir James Steuart, and Adam Smith / Ikuo Omori -- Adam Smith's politics of taxation: reconsideration of the image of 'Civilized Society' in the Wealth of Nations / Keiichi Watanabe -- The main themes and structure of Moral Philosophy and the formation of Political Economy in Adam Smith / Shoji Tanaka -- Civilization and history in Lord Kames and William Robertson / Kimihiro Koyanagi -- Liberty and Equality: Liberal Democratic Ideas in John Millar / Hideo Tanaka -- Dugald Stewart at the final stage of the Scottish Enlightenment: natural jurisprudence, political economy and the science of politics / Hisashi Shinohara -- Adam Smith in Japan / Hiroshi Mizuta.
Includes 1 errata slip.
Includes bibliographical references and index.
aia 18/09/13, rpm 23/10/13
Loan
Keywords: Economics -- Scotland -- History; Economists -- Scotland -- Biography; Philosophy, Scottish; Scotland -- Intellectual life; Enlightenment -- Scotland; Smith, Adam, -- 1723-1790.; Hume, David, -- 1711-1776.; Fletcher, Andrew, -- 1655-1716.; Hutcheson, Francis, -- 1694-1746.; Stewart, Dugald, -- 1753-1828.